Nanoparticles Affect the Expression Stability of Housekeeping Genes in Plant Cells - Selvakesavan RK (Dove Medical Press, 2020)
Rajendran K Selvakesavan, Gregory Franklin Institute of Plant Genetics of the Polish Academy of Sciences, Poznan 60-479, PolandCorrespondence: Gregory Franklin Tel +48 61 655 0266Email fgre@igr.poznan.plPurpose: We report on the expression stability of several housekeeping/reference genes that can be used in the normalization of target gene expression in quantitative real-time PCR (qRT-PCR) analysis of plant cells challenged with metal nanoparticles (NPs).Materials and Methods: Uniform cell suspension cultures of Hypericum perforatum were treated with 25 mg/l silver and gold NPs (14– 15 nm in diameter). Cells were collected after 0.5, 4.0, and 12 h. The total RNA isolated from the cells was analyzed for the stability of ACT2, ACT3, ACT7, EF1-α, GAPDH, H2A, TUB-α, TUB-β, and 18S rRNA genes using qRT-PCR. The cycle threshold (Ct) values of the genes were analyzed using the geNorm, NormFinder, BestKeeper, and RefFinder statistical algorithms to rank gene stability. The stability of the top-ranked genes was validated by normalizing the expression of HYP1.Results: The expression of the tested housekeeping genes varied with treatment duration and NP types. EF1-α in gold NP treatment and TUB-α and EF1-α in silver NP treatment ranked among the top three positions. However, none of the genes retained their top ranking with time and across NP types.Conclusion: EF1-α can be used as a reference for treatment involving both silver and gold NPs in H. perforatum cells. TUB-α can be used only for silver NP-treated cells. The expression instability of most of the housekeeping genes highlights the importance of systematic standardization of reference genes for NP treatment conditions to draw proper conclusions on the target gene expression.Keywords: nanoparticle, plant cell, Hypericum, gene expression, reference gene, quantitative real-time PCR